THE INFLUENCE OF DISTRIBUTED GENERATION INSTALLATION ON THE REDUCTION OF POWER LOSSES IN MEDIUM HIGH VOLTAGE - Handoko, Adi; Gianto, Rudy; Fitriah, Fitriah (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
This research investigates the impact of installing Distributed Generation (DG) on power losses in the feeder. The study uses the Newton-Raphson method in a power flow study to determine bus voltage values and power flow for all DG installation scenarios. The research is conducted on Raya 10 and Kijing Feeders, considering two DG installation scenarios: scenario 1 with 1 DG addition and scenario 2 with 2 DG additions. For Raya 10 feeder, DG installations at buses 91 and 91+92 result in reducing power losses by 35.64% and 55.35% for active and reactive power, respectively. In the Kijing feeder, DG installations at buses 35 and 35+48 lead to reductions of power losses by 40.98% and 67.02% for active power in scenarios 1 and 2, respectively. Reactive power also sees reductions of 41.6% and 68.73% in consecutive scenarios. In conclusion, DG installation in medium voltage networks (MVN) has a significantly positive impact on the voltage profile and power losses. More DG units in a feeder improve the voltage quality and reduce power losses. These findings highlight the potential of DG integration in enhancing the efficiency and sustainability of electrical power systems.